2022
DOI: 10.1007/s10389-022-01738-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adult shift and non-shift workers’ physical activity and sleep behaviours: cross-sectional analysis from the Household Income and Labour Dynamics of Australia (HILDA) cohort

Abstract: Aim This study compares the pattern of physical activity and sleep between shift and non-shift workers using a novel physical activity–sleep index. By drawing from a diverse occupational population, this research aims to reduce any occupational specific biases which are prevalent in shift-work research. Subject and methods Current data included 7607 workers (shift workers n = 832) from the Household Income and Labour Dynamics of Australia cohort study. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…One of the possible strategies is to look for suitable instruments for each group in order to apply the instrumental variables method appropriately. Additionally, all sleep data used in this paper were self-reported, which can be subject to recall bias; Fenwick et al (2022) had proposed the usage of accelerometers to overcome such bias.…”
Section: Finding Summary and Discussionmentioning
confidence: 99%
“…One of the possible strategies is to look for suitable instruments for each group in order to apply the instrumental variables method appropriately. Additionally, all sleep data used in this paper were self-reported, which can be subject to recall bias; Fenwick et al (2022) had proposed the usage of accelerometers to overcome such bias.…”
Section: Finding Summary and Discussionmentioning
confidence: 99%
“…Lastly, it's important to note that all sleep data used in this study were self-reported, which can be subject to recall bias. The use of accelerometers, as proposed by Fenwick et al (2022), could improve the accuracy of sleep data in future studies.…”
Section: Finding Summary Discussion and Conclusionmentioning
confidence: 99%
“…A few studies found strong associations between mental health and sleep quality. For example, using data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey, Duncan et al (2022) found that individuals aged 18 and above with insomnia had significantly higher odds of having poor mental health compared to individuals without insomnia. In another Singaporean study on 329 full-time workers, Dunleavy et al (2019) also reported an association between subjective sleep quality and impaired mental health.…”
Section: Introductionmentioning
confidence: 99%